ОНКОЛОГИК БЕМОРЛАР ҲАЁТ СИФАТИНИ ТАДҚИҚ ҚИЛИШНИНГ АЗАРИЙ ЖИҲАТЛАРИ - Уразбаева, Д.А. (SCIENCE and SOCIETY, 2022)
In thes article analyzed the problem of the need for study of the quality of life of cancer patients. In particular, the concept of quality of life, the importance of studying the quality of life of oncological patients, the components that make up the quality of life are translated. It also highlights the creation of the concept of patient quality of life by various scientists.